2021
DOI: 10.3390/nu13082551
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Bovine Colostrum in Pediatric Nutrition and Health

Abstract: Bovine colostrum (BC), the first milk produced from cows after parturition, is increasingly used as a nutritional supplement to promote gut function and health in other species, including humans. The high levels of whey and casein proteins, immunoglobulins (Igs), and other milk bioactives in BC are adapted to meet the needs of newborn calves. However, BC supplementation may improve health outcomes across other species, especially when immune and gut functions are immature in early life. We provide a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 318 publications
(492 reference statements)
0
38
0
1
Order By: Relevance
“…Milk is a natural substance that has been consumed by mankind for a long time, and it is also known to contain many immune substances, which have been shown to contribute to the development and growth of the newborn's intestines. [25][26][27] Recently, many research studies have reported that exosomes extracted from various types of milk are actually effective in alleviating the symptoms of IBD. [28][29][30] Milk has different ingredients depending on the time of breastfeeding, and among them, colostrum is known to contain a lot of essential nutrients, growth factors, and immune modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Milk is a natural substance that has been consumed by mankind for a long time, and it is also known to contain many immune substances, which have been shown to contribute to the development and growth of the newborn's intestines. [25][26][27] Recently, many research studies have reported that exosomes extracted from various types of milk are actually effective in alleviating the symptoms of IBD. [28][29][30] Milk has different ingredients depending on the time of breastfeeding, and among them, colostrum is known to contain a lot of essential nutrients, growth factors, and immune modulators.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue of Nutrients , “The Use of Bovine Colostrum in Medical Practice and Human Health” contains five review articles covering various aspects of the potential use of BC, including its main constituents and uses [ 1 ], use in gastrointestinal health and disease [ 2 ], sports nutrition [ 3 ], pediatrics [ 4 ], and immune support [ 5 ]. It also includes a systematic review of its clinical use [ 6 ] and an original research article examining its effects on enteric bacteria [ 7 ].…”
mentioning
confidence: 99%
“…Sangild and co-workers reviewed the evidence of use of BC in pediatric nutrition and health [ 4 ] and included a description of the value of the premature pig model as a surrogate for the human condition. There are several theoretical reasons why BC might have value for conditions affecting the newborn, including the fact that the gut lumen is probably more permeable to passage of intact proteins than the adult human gut.…”
mentioning
confidence: 99%
See 2 more Smart Citations